ANALISA PENGARUH KUALITAS BATUBARA TERHADAP BIAYA PEMBANGKITAN (STUDI KASUS DI PLTU REMBANG) - Agus Adhi Nugroho (MEDIA ELEKTRIKA, 2014)
Coalisone of the sourcesof energythat are widely usedinpower generation. Indonesiancoal productionas much as254milliontons in 2009as much as75% is exported, while the remaining25% for domestic consumption. Since much ofhigh-gradecoal(coal highrange) wereexportedout of the countrymakes theplantsin Indonesiawereoperating usingwith alow qualitycoal. The results ofthe analysis carried outinPLTU RembangofSeptember-November 2013can be concludedthatthe lower thecalorific valueof coalisusedthe higher themass flow rateof coal, thesteammass flow rateisrelativelythe same. The higherthe load, the coalmass flow rateis also higher,the specificfuelconsumption(kg /kWh) was decrease,theheatratewas decrease. However,the thermalefficiencywas increase. When theload of180MWto 250MWmoreefficientuseof coalcomposition100% LRC. Ata loadof 200MWto 250MWmoreefficientuseof coalcomposition of25%MRCand75% LRC. From theaverage value ofthe price ofproduction, moreefficientuseof coalcomposition100% LRC, butwiththecompositioncan notachievethe highestload. When viewedfrom theaverage valuethatcanmeet thehighestload, themore efficientisbyusing thecoalcomposition of50% MRC and50% LRC. Keywords: PLTU Rembang, Heatrate, ThermalEfficiency.